THE IMPACT OF TOURISM ON THE ECONOMIC GROWTH IN THE MEDITERRANEAN COUNTRIES: EVIDENCES FROM HIDDEN PANEL COINTEGRATION TEST - Süleyman Bolat; Abdulnasser Hatemi-j; Murat Belke (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The effect of tourism on economic growth is capturing the attention of researchers and policy makers worldwide. Many countries, both developed and developing ones, are systematically putting forward crucial strategies in order to promote their tourism industry with the main goal of achieving enhanced economic growth. Our main objective is to test for the potential asymmetric interaction between economic growth and tourism for a panel consisting of fourteen Mediterranean countries that covers the sample period 1995-2017 using hidden panel cointegration and asymmetric panel causality tests as developed by Hatemi-J (2020a; 2020b). Our empirical investigations indicate that there are indeed asymmetric impacts within our panel system. The impact of an increase in tourism on economic growth is stronger in the absolute terms compared to the impact of a corresponding decrease in tourism on growth.